Business Model Canvas: Hello Meow Enterprise / Syaidatul Umairah Solehah Abas - Abas, Syaidatul Umairah Solehah (2020)
The Business Model Canvas (BMC) is a strategic management tool to quickly and easily define and communicate a business idea or concept. It is a one-page document which works through the fundamental elements of a business or product, structuring an idea in a coherent way. The right side of the BMC focuses on the customer (external), while the left side of the canvas focuses on the business (internal). This BMC is used to have a great explanation about Hello Meow Enterprise